Potential of Wind Energy in Albania and Kosovo: Equity Payback and GHG Reduction of Wind Turbine Installation - Qafleshi, Mevlan; R. Kryeziu, Driton; Aliko, Lulezime (International Journal of Renewable Energy Development, 2015)
The energy generation in Albania is completely from the hydropower plants. In terms of GHG emissions this is 100% green. In Kosovo 97% of energy is generated from lignite fired power plants. Apart the energy generation, the combustion process emits around 8000 ktCO2/yr and 1.5 Mt of ash in the form of fly and bottom ash. In both countries there is no MWh power generated from wind energy, i.e. this energy source is not utilized. Here, a proposed project for five locations in Albania and Kosovo has been analyzed in detail with the aim of installing a 1kW wind turbine off-grid. The method of study is based on the application of RETScreen International program software. This proposed model is intended to replace a base case- a diesel generator with installed capacity 7kW. The locations are selected three in Albania: Vlora, Korça and Elbasan, and two in Kosovo: Prishtina and Prizren. All are in different altitudes. By the calculation of RETScreen program, it has been analyzed the feasibility of the proposed projects by installing a wind turbine at hub’s height 20m. The climate data for each location were retrieved by the RETScreen program from NASA. Generally, the calculation of financial parameters for the investments came out to be positive, the impact of GHG reduction very significant. A 5500 USD investment for the implementation of proposed case showed an equity payback time of 2-3 yrs and GHG reduction of 2.2 tCO2/yr. The electricity delivery to load only from this 1 KW wind turbine resulted to be between 1.6-17 MWh/yr.